2016
DOI: 10.1007/s00330-015-4179-0
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid volume: Rapid MR-based assessment at 28-32 weeks gestation

Abstract: • MR projection hydrography can be used to estimate amniotic fluid volume. • MR projection hydrography relies on the T2w signal from amniotic fluid. • Amniotic fluid volume (AFV) is more accurately assessed than with ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…We report a range of normative amniotic fluid volumes in the second and third trimesters of pregnancy, adding to the limited studies on this topic in fetal MRI 52 , 53 . In clinical practice, US is still the main modality used to assess amniotic fluid volume, but its accuracy is controversial 53 , 54 , 55 . A previous study had shown that MRI is a more accurate predictor of amniotic fluid volume compared to US 53 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We report a range of normative amniotic fluid volumes in the second and third trimesters of pregnancy, adding to the limited studies on this topic in fetal MRI 52 , 53 . In clinical practice, US is still the main modality used to assess amniotic fluid volume, but its accuracy is controversial 53 , 54 , 55 . A previous study had shown that MRI is a more accurate predictor of amniotic fluid volume compared to US 53 .…”
Section: Discussionmentioning
confidence: 97%
“…In clinical practice, US is still the main modality used to assess amniotic fluid volume, but its accuracy is controversial 53 , 54 , 55 . A previous study had shown that MRI is a more accurate predictor of amniotic fluid volume compared to US 53 . We did not observe a strong temporal evolution of amniotic fluid over GA, likely due to the highly dynamic nature of the production and resorption of amniotic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Although 3D ultrasound is more accessible and less expensive compared to MRI, it cannot possibly achieve the same. Ultrasound measurements can also be influenced by operator technique . Therefore, many studies have focused on the role of MRI for lateral ventricular volumetric measurement .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound measurements can also be influenced by operator technique. 19 Therefore, many studies have focused on the role of MRI for lateral ventricular volumetric measurement. [8][9][10][12][13][14][15] Some researchers have measured lateral ventricular volumes by manual MSP, 8,12,13 whereas others have estimated those volumes from 3D reconstructed volumetric datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation